Os exercícios nos livros didáticos de geografia destinados ao ensino primário no Brasil: uma discussão metodológica (1880 – 1930) - Ferreira, Joseane Abílio de Sousa (2017)
When we dare to tread the paths of the History of Education is to think, as soon as we can, that our productions are part of this History, building their marks and temporalities. It means that our productions are immersed in the process of organization of this field, recurrently marked by times, spaces and History of Education marks instituted itself that rises from areas and specificities of the field in each historical period. The study of school disciplines is part of the study of school culture, since school’s knowledge is a specific construction of the educational practices of the school, because it has its own characteristics and, therefore, presents other forms of knowledge (CHERVEL, 1990). Thus, aware of the responsibility of conducting studies of this nature, we seek to discuss from a specific type of didactic material: the Geography textbooks, having as object of study, the exercises. In our considerations, we find that this type of book involves knowledge that comes from different instances, but they are intertwined in the production's movements and constructions of this material object (BITTENCOURT, 2003), which, historically, they're constituted from Pedagogical conceptions and knowledge of the school culture of a certain time (HÉBRARD, 1990). So, our thesis proposal sought to discuss the methodologies applied to primary education in the discipline Geography between the years of 1880 and 1930, specifically about the role of exercises in textbooks, in an attempt to understand how they arose and how they interfered or not in the way of teaching Geography. In our study, we assumed that there was indication of the exercises as a new teaching method for the school as a whole, and that their presence in Geography classes represented the search for methodological innovations in Geography textbooks for primary education. Therefore, we hold the statement that exercises had a decisive role in the attempt to replace the text marked by explicit questions and answers in the books, by a text that slowly adopts the exercises as an expression of teaching methods capable of interfering in the proposal to make teaching less decorative and mnemonic. In our analyses, we verified that in the context of primary school, the exercises were present as an indispensable complement in the composition of textbooks and, therefore, in the teaching of Geography. Also, the idea of adoption the exercises in textbooks had as main purpose the search to introduce practical exercises and of observation that could try to break with the catechism method that prevailed in the books and in the school with a whole. In our considerations, we recognize and affirm the debate in favor of the insertion of the exercises in the primary education, and that these, even if slowly, interfere in the composition of the didactic works and, consequently, in the construction of the geographical knowledge. However, we noted that the presence of the mnemonic method, which marks the primary school culture with the principles of memorization methods, was still very strong.